The Role Expenditure of Marketing to Achieve Customer Satisfaction in Companies Insurance of Iraq - Zainab Sadeek Abraheem AL-Ameri (Journal of Madenat Alelem University College, 2020)
The research aims at identifying the relationship between increasing insurance companies’ spending on insurance services and achieving customer satisfaction by analyzing the amount of marketing expenses for marketing activities and their role in increasing revenues. In order to achieve this objective, the researcher used a sample of Iraqi insurance companies published their financial lists in the Iraqi market for securities for the financial years (2015-2016) through analyzing the expenditure data for marketing expenses and revenue achievement. In addition, the research was enhanced by a three- Distributed to the research sample and after analyzing the answers, the research objectives are achieved. The most important finding is that there is a strong correlation between increasing marketing spending and increasing revenue in insurance companies, which is an important indicator of increasing customer satisfaction in these companies. And the most important recommendation is the need for Iraqi insurance companies to increase attention to marketing activities for the purpose of showing insurance services in a manner appropriate to the requesting parties and to achieve the desire of the customer to obtain them.